2006
DOI: 10.1177/1090198106289002
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of School Gardens on Students and Schools: Conceptualization and Considerations for Maximizing Healthy Development

Abstract: There are thousands of school gardens in the United States, and there is anecdotal evidence that school garden programs can enhance students' learning in academic, social, and health-related domains. There has been little rigorous research, however, on the effects of school gardens or on the factors that promote the sustainability of these programs. This review draws on ecological theory to conceptualize school gardens as systemic interventions with the potential for promoting the health and well-being of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
232
0
31

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(286 citation statements)
references
References 34 publications
9
232
0
31
Order By: Relevance
“…While substantial research has been conducted to show that healthy diets, specifically diets high in F&V, are linked to reductions in obesity and obesity-related diseases such as type 2 diabetes and cardiovascular risk factors (40,41) , more studies examining the direct impact of a garden-based programme on obesity and related diseases are warranted. Considering Ozer's evaluation framework in 2007 (11) , there are multiple pathways by which school garden programmes may potentially strengthen the healthy development of students, including dietary intake, academic achievement/engagement and a sense of connection to schools, while enhancing the relationship of the school to the family and broader community. However, the majority of the garden programmes have primarily focused on the student outcomes, mainly dietary behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While substantial research has been conducted to show that healthy diets, specifically diets high in F&V, are linked to reductions in obesity and obesity-related diseases such as type 2 diabetes and cardiovascular risk factors (40,41) , more studies examining the direct impact of a garden-based programme on obesity and related diseases are warranted. Considering Ozer's evaluation framework in 2007 (11) , there are multiple pathways by which school garden programmes may potentially strengthen the healthy development of students, including dietary intake, academic achievement/engagement and a sense of connection to schools, while enhancing the relationship of the school to the family and broader community. However, the majority of the garden programmes have primarily focused on the student outcomes, mainly dietary behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…At about the same time, the paucity of empirical evidence on effectiveness of school gardens was revealed in a systematic review by Ozer (11) , which found only five separate studies on the health impacts of school gardens. Ozer recognized the emergence of school gardens as 'learning laboratories' in the USA and the need for a conceptual framework upon which to evaluate their impact on health.…”
mentioning
confidence: 99%
“…The sustainability of the gardens was important for the success of the intervention and required a long-term commitment (Ozer, 2007).The regional advisors had expertise and experience to link gardening and growing activities to the National Curriculum and to run staff training sessions for teachers. They worked directly with teachers and pupils.…”
Section: Rhs-led Interventionmentioning
confidence: 99%
“…Repeated exposure to FV can have a positive impact on liking and intake (Anzman-Frasca, Savage, Marini, Fisher, & Birch, 2012;Cooke, 2007). Gardening can provide opportunities for FV tasting and for learning in an interactive manner how fruit and vegetables are grown and their benefits to health (Ozer, 2007). However, there is limited high quality research evaluating the impact of gardening on children's FV intake, and it has provided mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Defined by the law, the School Meals Program is -in addition to providing the availability of high-quality school meals -also aimed at learning healthy habits; raising awareness about sustainable consumption, optimal growth and cognitive development; and developing responsible attitudes towards health and the environment (20) . Reviews of school nutrition interventions in other countries indicate that most of them are oriented either to healthy nutrition education (49)(50)(51) or other interventions such as school lunches, school canteens (52,53) , vending machines (54) , or specific practices such as school breakfast programmes (55,56) and school gardens (57) . Some interventions tend to focus only on specific foods, such as the School Fruit Scheme (58)(59)(60) , or specific dietary outcomes, such as decreased consumption of Significance obtained by ANOVA test: *P < 0·05; **P < 0·01; ***P < 0·001.…”
Section: Discussionmentioning
confidence: 99%